1998
DOI: 10.1590/s0102-311x1998000200015
|View full text |Cite
|
Sign up to set email alerts
|

O perfil epidemiológico do uso de drogas entre estudantes de 1º e 2º graus da rede estadual de ensino de Cuiabá, Brasil, 1995

Abstract: A cross-sectional survey was conducted on a sample of 1,061 students to determine the epidemiological profile of drug abuse among elementary and high school students in the State public school system in Greater Metropolitan Cuiaba, Mato Grosso, Brazil, in 1995. Results showed drug abuse among both male and female students (27. 2% and 24.1%, respectively). Drug abuse was more common in students over 18 years of age (27.1%), with grade/age discrepancies (70.7%), with higher classroom absenteeism (44.6%), and wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0
20

Year Published

2004
2004
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 0 publications
1
11
0
20
Order By: Relevance
“…El consumo de anfetaminas 128 y tranquilizantes 119,128 ha sido más frecuente en adolescentes de estratos altos. En estudios en los que se ha indagado el consumo de drogas en general (alcohol, tabaco y sustancias ilegales), se ha observado que éste es más elevado en los estratos altos 124,125,130 . En tres estudios 119,128,131 se reportó que el uso de inhalantes es más frecuente en sujetos de estratos bajos.…”
Section: Clase Ocupacionalunclassified
“…El consumo de anfetaminas 128 y tranquilizantes 119,128 ha sido más frecuente en adolescentes de estratos altos. En estudios en los que se ha indagado el consumo de drogas en general (alcohol, tabaco y sustancias ilegales), se ha observado que éste es más elevado en los estratos altos 124,125,130 . En tres estudios 119,128,131 se reportó que el uso de inhalantes es más frecuente en sujetos de estratos bajos.…”
Section: Clase Ocupacionalunclassified
“…5 Several studies using anonymous self-administered questionnaires have been carried out with the objective of studying the prevalence of drug use. 3,8,10,11,17,18 The Brazilian Center for Information on Psychotropic Sampling was systematic, stratified (public and private schools, ensino fundamental (1 st -8 th grades) and ensino médio, and day and night shifts), and with a probability proportional to the size (number of students) of all schools in the urban area of the city with ensino médio. The sampling universe was composed of 24 schools, of which 12 were run by the state government, 9 were private, two were federal, and one was municipal, and comprised 27,990 students enrolled between 5 th and 11 th grades, which correspond approximately to the 10-19 years age group.…”
Section: Introductionmentioning
confidence: 99%
“…14,16 The Brazilian literature highlights especially the importance of sociodemographic factors, which are the subject of most studies. 10,11,17,18 In addition to these factors, Carvalho et al, 6 in a national sample of students, identified domestic violence and the quality of family relationships as important factors related to drug use, while Baus et al 3 found an association between drug use and parents' divorce and not living with parents.…”
Section: Introductionmentioning
confidence: 99%
“…An indication of the magnitude of this use may be obtained from epidemiological surveys, which are essential to the framing of public policies and are internationally acknowledged as useful (1)(2)(3)(4)(5)(6)(7). Many regional studies in Brazil have expressed concern over the use of psychotropic drugs among students (8)(9)(10)(11)(12)(13)(14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%